Genomic reorganization by IS26in ablaNDM‐5‐bearing FII plasmid ofKlebsiella pneumoniaeisolated from a patient in Japan. Issue 9 (September 2018) - Takeuchi, Dan; Akeda, Yukihiro; Yoshida, Hisao; Hagiya, Hideharu; Yamamoto, Norihisa; Nishi, Isao; Yoshioka, Nori; Sugawara, Yo; Sakamoto, Noriko; Shanmugakani, Rathina Kumar; Deguchi, Matsuo; Tomono, Kazunori; et al.
Abstract : N/A: An NDM‐5‐producing Klebsiella pneumoniae ST147 strain was isolated from a Japanese patient who had not travelled abroad in at least 5 years. Whole‐genome sequencing revealed a genomic rearrangement in an FII plasmid harbouring bla NDM‐5 due to the replicative transposition of IS 26 . A hypothetical structure was proposed for its ancestral plasmid, and comparative genomic analysis of the plasmid suggested the dissemination of structurally similar plasmids harbouring bla NDM‐5 in Asian and Middle Eastern countries.